ANALISIS KERAWANAN LONGSOR BERBASIS SPASIAL DI KAWASAN TAMAN NASIONAL BANTIMURUNG BULUSARAUNG - Chaeril Chaeril; Amir Tjoneng; Saida Saida (Percetakan Umi Toaha Makassar, 2018)
This research was conducted with the aim of: 1) To identify the pattern (mapping) of prone landslide in Bantimurung Bulusaraung National Park, 2) To compile the analyze of prone landslide classification in Bantimurung Bulusaraung National Park, 3) To plan a strategy which can be applied for minimalizing the prone landslide in Bantimurung Bulusaraung National Park. Research was conducted on two regencies located in Bantimurung Bulusaraung National Park, Pangkep and Maros. Research was conducted from April to July 2017 using the secondary data which proccees by SIG and count by Storie’s Index method. As the factors are rainy drops, soil type, slope area, geology type, vegetation/land cover and human. The advanced analyze considering the zonation of Bantimurung Bulusaraung National Park. The results of analyzing, are 1) The research’s area in Maros contains prone and very prone wider than in Pangkep, 2) the soil type, geology type and slope area find in very prone landslide’s area, 3) The traditional zone which contains prone class and very prone class is in Mallawa, 4) Similarly condition for special zone which contains prone class and very prone class is in Mallawa. The strategy can be applied according to analyzing by Storie Index, are 1) planting and rehabilitation in open area, 2) the using of farm area in slope and steep area, applied by terraces model, 3)making socialization for the community in Prone Area and Very Prone Area, early anticipating landslide case